Simultaneous localization of cosmids and chromosome R-banding by fluorescence microscopy: application to regional mapping of human chromosome 11. - Dorra Chérif; Cécile Julier; Olivier Delattre; Josette Derré; G.M. Lathrop; Roland Berger (1990)
A technique for nonradioactive in situ hybridization on human metaphase chromosomes has been developed to localize human cosmid clones. The simple procedure using two fluorescent dyes (fluorescein and propidium iodide) allows the simultaneous identification of chromosomal R-bands and hybridization signal in a single screening of the slides. This technique has been used for rapid correlation of the genetic and physical map of chromosome 11q13-qter in the region of genes responsible for ataxia-telangiectasia and tuberous sclerosis.